2018
DOI: 10.1021/acs.jctc.8b00544
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Free Energy Calculations across Different Molecular Simulation Software Packages

Abstract: Alchemical free energy calculations are an increasingly important modern simulation technique to calculate free energy changes on binding or solvation. Contemporary molecular simulation software such as AMBER, CHARMM, GROMACS, and SOMD include support for the method. Implementation details vary among those codes, but users expect reliability and reproducibility, i.e., for a given molecular model and set of force field parameters, comparable free energy differences should be obtained within statistical bounds r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
125
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 96 publications
6
125
0
Order By: Relevance
“…The latter, in particular, requires specifying force field parameters and partial charges, but also other components of the simulation, such as ion concentrations and the treatment of long-range interactions (e.g., PME, reaction field, Lennard-Jones cutoff, dispersion correction). Treating long-range interactions equivalently is particularly challenging due to differences in functional forms, implementations, and options supported by the various software packages, including small discrepancies in the value of the Coulomb constant [29,30]. Establishing a set of simulation settings that minimizes these differences does not prevent systematic bias due to sampling issues, but it makes it possible to detect by comparing calculations performed with independent methods and/or starting from different initial configurations.…”
Section: Comparing the Efficiency Of Methods Requires Eliminating Conmentioning
confidence: 99%
“…The latter, in particular, requires specifying force field parameters and partial charges, but also other components of the simulation, such as ion concentrations and the treatment of long-range interactions (e.g., PME, reaction field, Lennard-Jones cutoff, dispersion correction). Treating long-range interactions equivalently is particularly challenging due to differences in functional forms, implementations, and options supported by the various software packages, including small discrepancies in the value of the Coulomb constant [29,30]. Establishing a set of simulation settings that minimizes these differences does not prevent systematic bias due to sampling issues, but it makes it possible to detect by comparing calculations performed with independent methods and/or starting from different initial configurations.…”
Section: Comparing the Efficiency Of Methods Requires Eliminating Conmentioning
confidence: 99%
“…They also suffer from inherent reproducibility issues due to the sensitivity of Newtonian dynamics to initial conditions and the lingering effects of such conditions if sampling is insufficient. 24,25 The purpose of this work is to formulate an efficient approximation for calculating molecular entropy in solution based only on physical and geometric arguments. Three models, S ω , S , and S α , are derived that rely only on such arguments-no empirically fitted parametersand elementary solvent properties (e.g., mass density).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made in previous work in different contexts. In a reproducibility study involving four different implementations of relative hydration free energy calculations, the authors found in many cases statistically significant ΔΔ differences on the order of 0.2 kcal/mol [27]. Systematic differences of the same order of magnitude were detected in a recent study comparing Monte Carlo and Molecular Dynamics sampling for binding free energy calculations [24], although, in this case, differences in water models and periodic boundary conditions might confound the analysis.…”
Section: Disagreements Between Methodsologies Impact Force Field Develmentioning
confidence: 90%
“…PME, reaction field, Lennard-Jones cutoff, dispersion correction). Treating long-range interactions equivalently is particularly challenging because different software packages typically make implementation decisions with the goal of increased performance, and available options such as supported cutoff algorithms and options, the functional form of switching functions, or even the value of the Coulomb constant may differ for various reasons [26,27]. As a consequence, it may be necessary to compromise to establish simulation settings that minimize obvious differences.…”
Section: Comparing the Efficiency Of Methods Requires Eliminating Conmentioning
confidence: 99%
See 1 more Smart Citation